SIMULASI TATA SURYA SEBAGAI MEDIA AJAR PADA PELAJARAN GEOGRAFI MENGGUNAKAN PAPERVISION3D - Erwina; Mohammad Fajar; Hamdan Arfandy (STMIK KHARISMA Makassar, 2018)
The aim of this research is to develop a solar system simulation software with its planet information as a learning and teaching media of geography subject, especially at senior high school. Data collection techniques are done through literature study, interview and software evaluation using Black Box method. The simulation software application is developed based on Kepler’s law of celestial mechanics and it is designed using Unified Modelling Language (UML) which involving use case diagram, class diagram, and activity diagram. While Document Type Definition (DTD) is used to define its database. The designed artifacts then implemented into computer programs using Adobe Flash, ActionScript 3.0 programming language, Papervision3D library, and eXtensible Markup Language (XML). The Papervision3D library is applied to form planets movement simulation, develop 3D solar system objects, apply texture or material into the objects, and insert 3DS object for ringed planets such as Saturnus and Uranus. The evaluation result shows that the designed simulation software is able to simulate solar systems consisting of the Sun and its planets, showing information from simulated objects, simulating Sun and Lunar eclipse. The software also provides practices feature for question and answer related to the solar systems and shows terms list in the solar system for Geography learning requirements.